Pendampingan Pemasaran Tempat Kost Berbasis Media Digital Untuk Warga Di Kelurahan Bulustalan Kota Semarang - Rizqi Fitri Naryanto; Mera Kartika Delimayanti; Muhammad Faizal Ardhiansyah Arifin; Bayu Bagas Hapsoro; Imanu Danar Herunandi (Universitas Lancang Kuning, 2023)
Semarang City is one of the provincial capitals which is very complete in terms of social, educational, economic, and other facilities. For this reason, many migrants live and settle temporarily in boarding houses. Bulustalan Village is a village located in the center of Semarang city and there are many office locations and higher education facilities around the area. For this reason, many employees and students are looking for a boarding house around the Bulustalan Village. In addition, in the Bulustalan Village area, especially in RT. 09/RW. 04, many have boarding houses, there are about 10 families out of 50 families who have boarding houses. During a pandemic like this, the boarding house business is experiencing the impact of a decrease in boarding house rents because many students live back in their hometowns. The boarding house business is one of the businesses for investment in the property sector. If not executed will cause losses because the boarding house will be damaged. In this digital era, product marketing can be done using digital media, namely through websites and social media. What's more, during a pandemic like this, someone tends to look for a boarding house using digital media. For this reason, marketing of boarding houses through digital media is one way that must be done to find the right potential users. The digital media used is the website media https://bapakkost.com/ which is the result of research from the head of service and marketing can be done with business Instagram social media. Training on the use of digital media for marketing boarding houses has been carried out and attended by more than 15 residents in RT09, Bulustalan sub-district. The digital media used is the website https://bapakkost.com/ and has also been provided in the form of a guidebook. This marketing can be done by the owner and not the owner of the boarding house by utilizing internet technology. The results of the questionnaire that had been given to the training participants stated that more than 75% of the participants agreed that the Bapakkost website could help market the boarding house. In addition, more than 65% of participants would recommend the Bapakkost website as a digital boarding house marketing tool. The output of this program is the result of the implementation of service activities in the form of news to national electronic media https://gossipnesia.com/ and youtube videos https://youtu.be/qgGbbu-4uPQ Keywords: digital media, training, marketing, website, boarding house, internet technology.